A method for hot-dip galvanizing of low-alloy high-strength structural steel
By adding alloy elements such as V, SN, Ni, Ti, AL to zinc bath, the problem of low alloy high -strength structural steel thermal immersion galvanization has been solved. The good corrosion resistance and adhesion of the coating are realized, and the overall performance of the workpiece is improved.
Patent Information
- Application Number
- CN202211407525.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-11-10
AI Technical Summary
During the hot-dip galvanizing process, low alloy high-strength structural steel has blackened the surface of the coating and reduced corrosion resistance and adhesion.
By adding alloy elements such as V, SN, Ni, Ti, AL to the zinc bath, regulate the component and ratio of the plating layer, inhibit the reactionability of silicon, control the growth of the plating, and improve the erosion resistance and adhesion of the coating.
It achieves good corrosion resistance and adhesion of the coating, improves the surface quality of the coating, reduces the cost of the zinc bath, and improves the overall performance of the workpiece.
Smart Images

Figure CN115896667B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel galvanizing, in particular to a method for hot-dip galvanizing of low-alloy high-strength structural steel. Background Art
[0002] Steel has been facing the problem of rust prevention since its birth, and steel corrosion and rust are the most common natural phenomena under the influence of the natural environment. At present, the hot-dip galvanizing process has been widely used to prevent steel corrosion and rust. The performance of the coating after hot-dip galvanizing of steel, that is, good coating adhesion and excellent coating processing and forming properties, are affected by many factors, such as the composition of the zinc bath, the temperature of hot-dip galvanizing, the immersion speed, the galvanizing time, the lifting speed, etc.
[0003] The Si content in low-alloy high-strength structural steel can reach 0.55%, which is much higher than that of ordinary carbon structural steel. Due to the reactivity of silicon, the growth of the Fe-Zn compound layer is difficult to control. Even after being lifted out of the zinc bath, the coating is still reacting rapidly, which significantly increases the thickness of the iron-zinc compound layer and consumes the free zinc layer, resulting in the thickness of the iron-zinc compound layer in the coating exceeding 95%, or even no free zinc layer. Therefore, color difference defects often appear on the surface of the coating, and the coating is prone to blackening, which greatly reduces the corrosion resistance and adhesion of the coating. The fundamental reason is that the coating is still reacting rapidly after being lifted out of the zinc bath.
[0004] Although adding Al and Ti can improve the surface quality of the hot-dip galvanized layer of low-alloy high-strength structural steel, the inhibitory effect on the silicon reactivity of the coating is not obvious. Studies have found that adding V and Sn alloy elements to the zinc bath can slow down the silicon reactivity of low-alloy high-strength structural steel. However, due to the high price of V and Sn elements, if the silicon reactivity is to be completely suppressed, a large amount of V and Sn needs to be added, resulting in excessive costs. At the same time, the addition of Sn elements has an adverse effect on the corrosion resistance of the coating, and the amount of addition must be strictly controlled.
[0005] The synergistic effect of multiple components can reduce the amount of alloy elements added. By adding Ni, the amount of elements such as V and Sn can be reduced. The synergistic effect can also effectively inhibit the reactivity of silicon, eliminate the color difference of the coating surface, prevent the blackening of the coating on structural steel parts, improve the corrosion resistance and adhesion of the coating, and reduce the cost of the zinc bath. Summary of the invention
[0006] The technical problem to be solved by the present invention is: in order to overcome the deficiencies in the prior art, the present invention provides a method for hot-dip galvanizing of low-alloy high-strength structural steel to solve the problem of surface blackening and decreased corrosion resistance and adhesion due to the presence of silicon reactivity during hot-dip galvanizing of low-alloy high-strength structural steel in the prior art.
[0007] The technical solution adopted by the present invention to solve the technical problem is: a method for hot-dip galvanizing of low-alloy high-strength structural steel, comprising the following steps:
[0008] Step (1), pre-galvanizing treatment: treating the surface of the structural steel substrate to prevent the molten zinc from completely reacting with the substrate during the subsequent hot-dip galvanizing process;
[0009] Step (2), hot-dip galvanizing: immersing the structural steel substrate that has completed the pre-galvanizing treatment into a zinc bath, so that the structural steel substrate reacts with the molten zinc to form an alloy coating on the substrate surface, thereby completing the hot-dip galvanizing;
[0010] The zinc bath includes the following raw materials in proportion by weight:
[0011] Zn: 99.585 to 98.67 parts, V: 0.04 to 0.1 parts, Sn: 0.3 to 1.0 parts,
[0012] Ni: 0.06 to 0.2 parts, Ti: 0.01 to 0.02 parts, Al: 0.005 to 0.01 parts.
[0013] Preferably, in step (1), the pre-plating treatment includes degreasing, pickling, water washing, plating assistance and drying.
[0014] Furthermore, the degreasing is alkaline degreasing, and the degreasing agent used is 15% NaOH solution.
[0015] Furthermore, the plating aid used in the plating is a zinc ammonium chloride plating aid solution, and the weight ratio of ammonium chloride to zinc chloride is 1:1.2 to 1:1.6.
[0016] Furthermore, the drying temperature is 80°C to 100°C.
[0017] Preferably, in step (2), the temperature of the hot-dip galvanizing is 430° C. to 460° C., and the time of the hot-dip galvanizing is 180 s to 300 s.
[0018] The beneficial effects of the present invention are as follows: the present invention has good controllability, and can enhance the corrosion resistance and adhesion of the coating, and change the surface quality of the coating by changing the components and ratio of the zinc bath during hot-dip galvanizing of steel. The prepared workpiece has good corrosion resistance, and the coating surface is bright, has excellent adhesion, and has an appropriate thickness. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0020] Figure 1 This is a microstructural morphology of the hot-dip galvanized alloy coating of the low-alloy high-strength structural steel prepared in Example 1.
[0021] Figure 2 This is a microstructural morphology of the hot-dip galvanized alloy coating of the low-alloy high-strength structural steel prepared in Example 2.
[0022] Figure 3 This is a microstructural morphology of the hot-dip galvanized alloy coating of the low-alloy high-strength structural steel prepared in Example 3.
[0023] Figure 4 This is a microstructural morphology of the hot-dip galvanized alloy coating of the low-alloy high-strength structural steel prepared in Example 4.
[0024] Figure 5 This is the microstructural morphology of the low-alloy high-strength structural steel obtained in Comparative Example 1 after hot-dip plating with pure zinc.
[0025] Figure 6 This is the microstructural morphology of the hot-dip galvanized alloy coating of the low-alloy high-strength structural steel prepared in Comparative Example 2.
[0026] Figure 7 These are surface photographs of the low-alloy high-strength hot-dip galvanized structural steels prepared in Example 1, Comparative Example 1, and Comparative Example 2.
[0027] Figure 8 It is the diffusion channel model of Fe-(Zn, V) reaction.
[0028] Fig. 9 Schematic diagram of the zinc-rich angular phase relationship of the Zn-Fe-Si-V quaternary system at 450℃ and the diffusion channel model of the interfacial reaction when the active steel is immersed in the Zn-V molten pool. DETAILED DESCRIPTION
[0029] Example 1
[0030] A hot-dip galvanizing method for low-alloy high-strength structural steel comprises the following steps:
[0031] Step (1) pre-galvanizing treatment: treating the surface of the structural steel parts to prevent the molten zinc from completely reacting with the parts during the subsequent hot-dip galvanizing process;
[0032] Pre-plating treatment includes the following steps:
[0033] a. Degreasing: Immerse the structural steel parts in degreasing liquid for degreasing. The degreasing liquid is 15% NaOH solution. The degreasing temperature is 25℃~50℃ to remove the grease adhered to the surface of the parts during processing, storage and transportation;
[0034] b. Pickling: Put the workpiece into 10% to 15% hydrochloric acid for pickling. Stir the workpiece appropriately during the pickling process and control the pickling temperature at 18℃ to 21℃ to remove the oxide scale and rust on the surface of the workpiece;
[0035] c. Rinse: Rinse the pickled parts with 95% alcohol;
[0036] d. Plating assistance: After pickling, the workpiece is immersed in a zinc ammonium chloride plating assistance solution with a certain composition to complete the plating assistance. The temperature of the plating assistance solution is 60℃~80℃. The function of plating assistance is to remove the iron salt or oxide remaining on the surface of the workpiece after pickling, so that the workpiece has the maximum surface activity when entering the zinc bath; at the same time, a layer of salt film is deposited on the surface of the workpiece, which can prevent the workpiece from rusting in the air during the period from the plating assistance pool to the zinc pot, and can also purify the liquid zinc where the workpiece is immersed in the zinc bath, so that the workpiece and the liquid zinc can quickly infiltrate and react;
[0037] The concentration of ammonium zinc chloride in the flux solution is controlled at 200 g / L to 400 g / L, and the weight ratio of ammonium chloride to zinc chloride is 1:1.2 to 1:1.6, wherein W FeCl2 <1%;
[0038] e. Drying: Dry the parts after plating to make the parts with plating agent as dry as possible. The drying temperature is 80℃~100℃;
[0039] (2) Hot-dip galvanizing: The workpiece that has completed the pre-galvanizing treatment is immersed in a zinc bath to react with the molten zinc to form an alloy coating on the surface of the workpiece, thereby completing hot-dip galvanizing. The hot-dip galvanizing temperature is 430℃~460℃, and the galvanizing time is controlled within 180s~300s;
[0040] The zinc bath includes the following raw materials in proportion by weight:
[0041] Zn: 99.294 parts, V: 0.06 parts, Sn: 0.5 parts,
[0042] Ni: 0.12 parts, Ti: 0.02 parts, Al: 0.006 parts.
[0043] The microstructure morphology of the hot-dip galvanized alloy coating of low-alloy high-strength structural steel prepared in Example 1 is shown in FIG. Figure 1 shown.
[0044] The hot-dip galvanizing method of Example 2, Example 3, Example 4, Comparative Example 1, and Comparative Example 2 is the same as that of Example 1, except that the components and proportions of the zinc baths of Example 2, Example 3, Example 4, Comparative Example 1, and Comparative Example 2 are different from those of Example 1 during hot-dip galvanizing.
[0045] The microstructure morphology of the low alloy high strength structural steel hot dipped with pure zinc obtained in the above examples and comparative examples is shown in Figure 2 to Figure 6 Surface photos of low alloy high strength hot dip galvanized structural steel obtained in Example 1, Comparative Example 1 and Comparative Example 2 are shown in Figure 7 shown.
[0046] The specific components and proportions of the zinc baths of Example 1, Example 2, Example 3, Example 4, Comparative Example 1, and Comparative Example 2 are shown in Table 1;
[0047] Table 1
[0048]
[0049] Experimental testing
[0050] The structural steel parts prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance and appearance quality tests of the coatings after hot-dip galvanizing, including alloy layer thickness, coating appearance quality, coating adhesion, and coating corrosion resistance.
[0051] The thickness of the alloy layer was measured by using a metallographic microscope. Three different photos of the same coating were taken at 200 times, and the average thickness of the coating was measured using a ruler.
[0052] The appearance quality of the coating is in accordance with the provisions of GB / T13912-2002 "Hot-dip galvanizing standard": the appearance quality indicators of the hot-dip coating mainly include that the main surface should be smooth, free of nodules, roughness and zinc thorns, no peeling, no leakage, and no residual flux slag. There should be no zinc nodules and zinc ash in the parts that may affect the use or corrosion resistance of the hot-dip galvanizing work. The present invention uses a 10x magnifying glass to observe the appearance quality of the coating.
[0053] The coating adhesion test refers to the standard GB / T1732-93, and the coating is tested using a paint film impact tester. The test sample is placed on the base of the paint film impact tester, and a fixed-mass hammer is dropped from a certain height to impact the punch, causing the coating and the substrate to deform. It can be a positive impact (the paint film is facing up) or a negative impact (the paint film is facing down). By gradually increasing the height of the hammer's drop, the numerical point where the coating is often damaged is measured.
[0054] The corrosion resistance of the coating is carried out in accordance with the standard GB10125-88. A neutral salt spray test is carried out using a salt spray test machine. The spray medium used is a 5% NaCl solution with a pH value of 6.5 to 7.2. During the experiment, the temperature in the salt spray chamber is controlled at (35±2)°C. After continuous spraying for 480 hours, the sample is taken out and the weight of the sample after removing the corrosion product is recorded to an accuracy of 0.0001g. According to the formula Calculate the corrosion rate v.
[0055] The test results of the coating properties of the steel prepared in this example are shown in Table 2:
[0056] Table 2:
[0057]
[0058] It can be seen from Table 2 that after the structural steel parts are hot-dip galvanized in zinc baths with different components and ratios, the appearance quality and performance of the coating obtained are different. The performance and appearance of the coatings of the steel materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 2 meet the national standards, and the corrosion resistance, surface finish, uniformity and adhesion are excellent, especially in Examples 1 and 2.
[0059] In the present embodiments 1-4, the growth of the alloy layer of the coating obtained by adding V, Sn, Ni, Ti and Al elements into the zinc bath is suppressed; the coating surface smoothness, coating surface adhesion and coating surface corrosion resistance are relatively excellent; in the present comparative example 1, the growth of the alloy layer of the coating obtained by not adding additional elements into the zinc bath is not suppressed; the coating surface is dark, and the coating surface adhesion and coating surface corrosion resistance are poor; in the present comparative example 2, the coating obtained by adding Ti and Al elements into the zinc bath is bright, but the coating surface adhesion and coating surface corrosion resistance are average.
[0060] By comparing the control example 1 and the control example 2, it can be seen that the appearance quality and corrosion resistance of the steel coating prepared by adding Al and Ti elements to the zinc bath in the control example 2 are improved to a certain extent, but the improvement is not obvious, and there is no significant change. Therefore, it is shown that adding a small amount of Al and Ti elements to the zinc bath has a certain impact on the appearance quality and performance of the coating, but the impact is small.
[0061] By comparing the zinc baths of Examples 1 to 4 in which V, Sn and Ni elements are added, and the zinc baths of Control Example 2 in which V, Sn and Ni elements are not added, it can be seen that the thickness of the alloy layer, the appearance quality of the coating, the adhesion of the coating and the corrosion resistance of the coating obtained by Examples 1 to 4 and Control Example 2 are quite different and have significant changes. The appearance quality, adhesion of the coating and the corrosion resistance of the coating of Examples 1 to 4 are better than those of Control Example 2. Therefore, adding V, Sn and Ni elements to the zinc bath of hot-dip galvanizing of steel can improve the adhesion, smoothness and corrosion resistance of the plated surface.
[0062] By comparing Example 1 in which V, Sn, and Ni elements are added to the zinc bath and Examples 2 to 4 in which less V, Sn, and Ni elements are added to the zinc bath than Example 1, it can be seen that the appearance quality and adhesion of the coatings prepared by Example 1 and Examples 2 to 4 are not very different, and there is no significant change, but the thickness of the alloy layer and the corrosion resistance of the coating are different, and there is a certain improvement. The thickness of the coating alloy layer and the corrosion resistance of the coating of Example 1 are better than those of Examples 2 to 4. Therefore, inhibiting the growth of the alloy layer during hot-dip galvanizing of steel has a positive effect on the corrosion resistance of the coating.
[0063] Based on the measured 450℃ isothermal section of Zn-Fe-V ternary system, the present invention adopts diffusion channel theory to explain the effect of V on hot-dip galvanizing. When Fe is plated into Zn-V alloy, since the metastable solubility of Fe in Zn is close to the ζ phase component, a diffusion channel Path I is formed, such as Figure 8 As shown in the figure; with the extension of the immersion time, the T phase replaces the ζ phase to become the equilibrium phase with the liquid zinc, so the T phase is formed at the interface between the ζ and liquid phases, and the diffusion channel cuts the conjugate line of the T+Liq two-phase region, and then skips the T+ζ+Liq three-phase region to enter the ζ+Liq phase region (PathⅡ), thereby effectively controlling the growth of the Fe-Zn alloy layer.
[0064] When the steel matrix contains a certain amount of Si, combined with the Zn-Fe-Si ternary phase diagram, the phase system of the Zn-Fe-Si-V quaternary system rich in Zn-Fe is extrapolated, and the schematic diagram is as follows: Fig. 9 As shown. Path0 in the figure is a diffusion channel explanation model for silicon reactivity. Since silicon has almost no solubility in the ζ phase, Si is enriched at the δ boundary, and the diffusion channel cuts the conjugate line of ζ+Liq, thereby bypassing the ζ phase. When the zinc pool contains a certain amount of V, since V has a strong binding energy with Si, and the solubility of Si in the T phase is greater than that in the ζ phase, the tendency of the diffusion channel to deviate to the Si-rich side decreases. As long as the diffusion channel does not bypass the ζ+T+Liq three-phase region (Path3), ζ+T can effectively prevent the zinc liquid from directly corroding the δ layer, thereby controlling the growth of the Fe-Zn alloy layer. However, once the diffusion channel deviates from the ζ+T+Liq three-phase region (Path1), it may be impossible to suppress silicon reactivity. When the diffusion channel is just on the ab line (Path2), the matrix composition fluctuates slightly, the silicon reactivity in the local area cannot be suppressed, and an explosive organization may be formed.
[0065] Therefore, after adding a certain amount of V to the zinc bath, the ternary compound T phase replaces the ζ phase to become a compound in equilibrium with liquid zinc. At the same time, due to the strong affinity between V and Si, the degree of deviation of the diffusion channel of the galvanizing reaction toward the Si-rich angle is reduced. As long as the diffusion channel does not deviate from the ζ+T+Liq three-phase region, the ζ or ζ+T layer can form a barrier layer, effectively inhibiting the occurrence of silicon reactivity and controlling the growth of the Fe-Zn alloy layer.
[0066] At the same time, V is chemically inactive at room temperature, is easily passivated, has strong corrosion resistance, does not react with air, water, non-oxidizing acids and strong alkali solutions. Adding V to the coating can effectively improve the corrosion resistance of the coating. Although V is an expensive alloy element, adding only a small amount of V will not significantly increase the production cost of the alloy.
[0067] Therefore, the present invention adjusts the amount of V by adding Sn, Ni, Ti, Al and other alloys on the basis of adding V to the zinc bath, which not only ensures the thickness of the free layer and suppresses the reactivity of silicon, but also has a low cost.
[0068] It can be seen that the steel prepared by the present invention has excellent coating performance. By adding V, Sn and Ni elements to the zinc bath of hot-dip galvanizing of the steel, the coating surface finish, coating surface adhesion and coating surface corrosion resistance can be improved, so that the prepared steel coating has more excellent performance.
[0069] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A hot dip galvanizing method for low alloy high strength structural steel, characterized in that: The following steps are involved: Step (1), pre-galvanizing treatment: treating the surface of the structural steel substrate to prevent the molten zinc from completely reacting with the substrate during the subsequent hot-dip galvanizing process; Step (2), hot-dip galvanizing: immersing the structural steel substrate that has completed the pre-galvanizing treatment into a zinc bath, so that the structural steel substrate reacts with the molten zinc to form an alloy coating on the substrate surface, thereby completing the hot-dip galvanizing; The zinc bath includes the following raw materials in proportion by weight: Zn: 99.585 to 98.67 parts, V: 0.04 to 0.1 parts, Sn: 0.3 to 1.0 parts, Ni: 0.06 to 0.2 parts, Ti: 0.01 to 0.02 parts, Al: 0.005 to 0.01 parts.
2. The hot-dip galvanizing method for structural steel according to claim 1, characterized in that: In step (1), the pre-plating treatment includes degreasing, pickling, water washing, plating assistance and drying.
3. The hot-dip galvanizing method for structural steel according to claim 2, characterized in that: The degreasing is alkaline degreasing, and the degreasing agent used is 15% NaOH solution.
4. The hot-dip galvanizing method for structural steel according to claim 2, characterized in that: The plating aid used in the plating aid is zinc ammonium chloride plating aid solution, and the weight ratio of ammonium chloride to zinc chloride in the zinc ammonium chloride plating aid solution is 1:1.2 to 1:1.
6.
5. The hot-dip galvanizing method for structural steel according to claim 2, characterized in that: The drying temperature is 80°C to 100°C.
6. The hot-dip galvanizing method for structural steel according to claim 1, characterized in that: In step (2), the temperature of hot-dip galvanizing is 430° C. to 460° C., and the time of hot-dip galvanizing is 180 s to 300 s.
Citation Information
Patent Citations
Method for producing hot-dip galvanized steel material, and hot-dip galvanized steel material
CN106661708A
Hot-dip galvanization system and hot-dip galvanization method
CN108884543A